Heterogeneity in the subjective well-being impact of access to urban green space. (November 2021) - Sharifi, Farahnaz; Nygaard, Andi; Stone, Wendy M.
Highlights: Higher urban green space access levels are associated with higher well-being levels. There is heterogeneity in urban green space's impact. Only large urban green spaces have a significant effect on well-being. Individuals with lower well-being levels benefit less from urban green space. Green corridors might enhance green space benefits for subjective well-being. Abstract: There is a growing body of literature on the impact of urban green space (UGS) on residents' subjective well-being (SWB). However, few studies analyze how SWB impacts of UGS may depend on the quality aspects of UGS, and even fewer studies analyze how impacts may vary across the different levels of SWB. Drawing on individual data from the Household, Income and Labour Dynamics in Australia (HILDA) survey over 2001-17 for Melbourne, this paper estimates a set of hedonic models of SWB to explain the heterogeneity in SWB impacts of UGS. The results show that the size of UGS matters and that UGS impact on SWB varies considerably across different well-being levels. Specifically, individuals with low levels of SWB, overall, demonstrate much less responsiveness to proximity to UGS than individuals with high levels of SWB. Unless combined with other determinants of SWB, we argue that conventional interpretations of urban planning ideals may exacerbate, rather than mitigate, social well-being inequality. Moreover, the design of UGS, such as green corridors, can help to emulate well-being enhancing dimensions of UGS in already built-up areas.